Deep-Dive on Malaysia’s Digital Services Trade - World Bank (Washington, DC, 2022)
The rapid expansion of digital technologies around the world has impacted many economic and social activities with increasingly reliable and fast Internet connectivity changing how people communicate, work, and live. Digital services have also played an important role in keeping the world connected and economies running during the COVID-19 pandemic. It is therefore crucial that countries implement proactive polices to become more digitalized and target the creation of an inclusive digital economy in order to foster sustainable and inclusive economic growth. Cross-border data transfer regulations also play an important role in supporting trade in digital services. The Malaysia digital economy report produced by the World Bank in 2018 examined three interrelated issues that are closely aligned with Malaysia’s own goal of becoming an e-commerce hub for the region. Building on this research agenda, this deep dive seeks to explain how the role of digital services trade can be enhanced to contribute to Malaysia’s competitiveness and integration into the global marketplace. The paper is structured as follows: section one gives introduction and context. Sections 2 and 3 benchmarks Malaysia’s digital preparedness (for example, in terms of Internet penetration ratios) against its structural, aspirational, and regional peers. Section 4 assesses the performance of Malaysia’s digital services trade and digital economy, including in sub-sectors such as e-commerce and FinTech which are both important elements of digitalization. Section 5 discusses the constraints to deeper integration and development of the digital sector in the Malaysian economy. Section 6 presents the main findings and makes policy recommendations.